MRI characteristics of the substantia nigra in Parkinson's disease: a combined quantitative T1 and DTI study. - Menke, R; Scholz, J; Miller, K; Deoni, S; Jbabdi, S; Matthews, P; Zarei, M (2009)
The substantia nigra contains dopaminergic cells that project to the striatum and are affected by the neurodegenerative process that appears in Parkinson's disease (PD). For accurate differential diagnosis and for disease monitoring the availability of a sensitive and non-invasive biomarker for Parkinson's disease would be essential. Although there has been notable progress in studying correlates of nigral degeneration by means of magnetic resonance imaging (MRI) in the past decade, MRI and analysis techniques that allow accurate high-resolution mapping of the SN within a clinically acceptable acquisition time are still elusive. The main purpose of the preliminary study was to evaluate the potential role of the driven equilibrium single pulse observation of T1 (DESPOT1) method for delineation of the SN and differentiation of PD patients from healthy control subjects (n=10 in each group). We also investigated whether additional measures that can be obtained with diffusion tensor imaging (DTI) can further improve the MRI-guided discrimination between PD patients and controls. Our results show that the DESPOT1 method allows for a clear visualisation of the SN as a whole. Volumetric comparisons between ten PD patients and ten healthy subjects revealed significantly smaller volumes in patients for both the left and the right sides when the whole SN was considered. Combining SN volumetry and its connectivity with the thalamus improved the classification sensitivity to 100% and specificity to 80% for PD (discriminant function analysis with leave-one-out cross validation). Combining DESPOT1 imaging and DTI could therefore serve as a diagnostic marker for idiopathic Parkinson's disease in the future.